Opioid agonist treatment is highly protective against overdose death among a U.S. statewide population of justice-involved adults. (2nd January 2021) - Krawczyk, Noa; Mojtabai, Ramin; Stuart, Elizabeth A.; Fingerhood, Michael I.; Agus, Deborah; Lyons, B. Casey; Weiner, Jonathan P.; Saloner, Brendan
ABSTRACT: Background : Persons with justice-involvement have high rates of opioid use disorder (OUD) and overdose and are a critical target of policy initiatives to improve access to evidence-based medications for OUD. However, less is known about what characteristics of justice-involved persons make them more or less likely to receive evidence-based care. Objectives : Focusing on a Maryland state-wide sample of justice-involved individuals, this study explores predictors of OUD treatment utilization and the relationship between referral source to treatment, treatment with opioid agonists, and risk of a fatal opioid overdose. Methods : Records were obtained for persons with arrests, incarcerations, and community supervision cases related to property/drug crimes in Maryland in 2015–2016 (N = 43, 842). Individuals were matched to records in three state databases: admissions to specialty substance use disorder treatment, buprenorphine prescriptions for office-based OUD treatment, and opioid overdose death records. Multivariate logistic regression was used to identify correlates of opioid agonist treatment utilization and overdose risk among justice-involved adults who received OUD treatment. Results : Of 43, 842 justice-involved adults (80% male), nearly 20% utilized OUD treatment. Of these, 58% received agonist medications. Those with polysubstance use diagnoses or referred to treatment directly by criminal justice sources were least likely to receive medications. Agonist medications reduced odds of fatal overdose by 60%. Conclusions : Opioid agonist treatment was highly protective against overdose among justice-involved individuals receiving treatment in the community, but many still lacked access to this type of care. Policies and interventions to promote the expansion of opioid agonist treatment in community settings that serve justice-involved persons are critical.